Unusual widening of Virchow-Robin spaces: MR appearance. - Ogawa, T; Okudera, T; Fukasawa, H; Hashimoto, M; Inugami, A; Fujita, H; Hatazawa, J; Shimosegawa, E; Noguchi, K; Uemura, K (American Journal of Neuroradiology, 1995)
MR in two patients with unusual widening of the Virchow-Robin spaces showed multiple cystic foci up to 2 cm in diameter along the perforating medullary arteries in the cerebral white matter, mainly in one cerebral hemisphere. These areas were of the same signal intensity as cerebrospinal fluid on all pulse sequences. In one patient, the cystic foci in the white matter were biopsied and histologically confirmed to be large Virchow-Robin spaces.